ANALISA PENGARUH HARGA, PROMOSI DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA "ONLINE SHOP" S-NEXIAN MELALUI FACEBOOK - Ristania, Novia; Justianto, Jerry S. (Journal of Business Strategy and Execution, 2013)
The emergences of Social Media provide all the ease to communicate just like real life. Activities that could be done by consumers also variety in Social Media, starting from search information about products, comparing other products until to make purchases online. Seeing this, many companies begin entering the social media for the benefit of their company, whether it is to increase the awareness, engagement to the customer, and even conduct online sales. S-Nexian is one of the companies that have been doing online sales through Facebook with the program "Online Shop". This research aims to investigate the influence of variable pricing, promotion and viral marketing on purchasing online decisions using a survey of the S-Nexian fans that have made a purchase online. Results from this study were the effect of variable pricing, promotion and viral marketing positive influence on purchase decisions through the "Online Shop" S-Nexian. Viral marketing was a variable that has most contributed. Through this research, the expectation of using Facebook as a tool to promote the "Online Shop" program of S-Nexian could be improved, because of every promotion could be directly received and prompt responded by consumers.